The Emergence of Islamic Neoliberalism in Turkish Political Economy: The Governance of Education Systems in Turkey. - Altinors, Gorkem (Journal of Balkan & Near Eastern Studies, 2025)
This article critically examines the rise of Islamic neoliberalism within Turkey's political economy, particularly its impact on the governance of education. With the Justice and Development Party (AKP) coming to power in 2002, Islamic neoliberalism emerged as a hegemonic project, challenging the secular foundations of modernization. This shift was legitimized through two processes: Islamism gained democratic credibility by distancing itself from secularism's association with military coups, while neoliberalism was promoted as a solution to state inefficiencies. Ostensibly, this model initially fostered economic growth and strengthened Turkey's EU candidacy, but by the 2010s, democratic backsliding and economic crises ensued. Using a critical global political economy framework, this article argues that AKP governance represents a continuous process, linking Islamic neoliberalism to Turkey's political and economic crises, and highlighting how promises of progress and growth led to authoritarianism and instability.